The Role of Katekisasi Sidi in Building Faith to Form the Character of Sidi Participants at HKBP Sukadame Pematang Siantar - Munthe, Bangun; Butarbutar, Imelda; Ginting, Rini Tiara (Bulletin of Science Education, 2023)
The aim of this research is to find out the extent of the role of Sidi Catechism in building faith to shape the character of Sidi participants at HKBP Sukadame. The research population was Sidi participants at HKBP Sukadame with a total of 46 people. This research uses a descriptive method while the data analysis used in hypothesis testing is Pearson Product Moment correlation and the data collection tool is a closed questionnaire for variables Pearson Product Moment correlation statistics, and from the correlation results obtained r = 0.372 with a determination test of 13.69% and to determine whether the correlation coefficient is significant at the real level (?) = 0.05. Then a t test is carried out with the testing criterion if tcountgreater than ttable(2.67) > (1.67) at the significance level of 1-0.05 with dk = n-2 then the hypothesis is accepted. In this way, it can be stated that there is a significant relationship between the role of Sidi Catechism in building faith and forming the character of Sidi participants at HKBP Sukadame. Keywords: Role of Katekisasi Sidi, Building Faith, Building Faith Sidi